Numerical investigation of rotor loads of a shipborne coaxial-rotor helicopter during a vertical landing based on moving overset mesh method - Dacheng Su; Guohua Xu; Shuilin Huang; Yongjie Shi (Engineering Applications of Computational Fluid Mechanics, 2019)
Coupled ship/coaxial-rotor simulations have been conducted to investigate the rotor loads of a shipborne coaxial-rotor helicopter during a vertical landing based on Reynolds-averaged Navier-Stokes (RANS) solver. In order to achieve two-way coupling and overcome the limitations of the momentum source method in solving the unsteady aerodynamic problems, the moving overset mesh method is employed to simulate the complex highly unsteady aerodynamic interactions between the lower/upper rotor, flight deck and hangar-door through the vertical descent. To identify pilot workload and control strategy during this phase, the results in terms of time-averaged and root-mean-square (RMS) rotor loads are discussed. The time-averaged loads show that the coaxial-rotor helicopter suffers an increase in thrust and a sharp decrease in torque difference between lower and upper rotors during the vertical landing. It suggests that the pilot has to reduce not only the collective control input, but also the differential collective pitch, to stabilize the heading of the coaxial rotors helicopter. The RMS results indicate that the aerodynamic loads of the lower and upper rotors could couple with each other, and may eventually magnify the overall unsteady loading levels of the coaxial rotor. In addition to the ground effect, the recirculation flow regime will get stronger and lead to a sharp increase in RMS roll as the rotor moves along the vertical descent path. Furthermore, the influences of hangar-door state and the location of landing spot are investigated. The findings imply that opening the hangar-door can significantly reduce the pilot workload, and descending a helicopter to a landing spot which is more closed to the hangar can decrease the RMS load levels, especially during the latter stage of vertical descent. However, the helicopter tends to be pulled towards hangar-door more easily due to greater reduction in pitch moment.